PELATIHAN PENGEMASAN DAN MANAJEMEN PEMASARAN IKAN PEDO BU SUSI DI DESA SUKOMORO KECAMATAN RAWAS ULU KABUPATEN MUSI RAWAS UTARA - Fitria Lestari; Yuli Febrianti; Nopa Nopiyanti; Reny Dwi Riastuti (Nusantara Hasana Berdikari, 2022)
Sukomoro Village is a village in the Rawas Ulu sub-district, North Musi Rawas Regency with fish fishermen as a livelihood. The abundance of fish is processed into products such as pedo fish. One of the pedo fish businesses in Sukomoro is Bu Susi's Pedo fish. In their daily life, the packaging and marketing carried out by this business is still manual, namely only with ordinary plastic and marketing is only at home, so that it is less well known by the wider community. Therefore, in this activity what is carried out is packaging and marketing management training. in Sukomoro village, especially Bu Susi's pedo fish business. The result of this activity is that the product packaging is better and Fish, marketing is carried out by placing it in a shop.